Interband electronic transitions and phase diagram of PbZr1−xTixO3 (0.05 ≤ x ≤ 0.70) ceramics: ellipsometric experiment and first-principles theory. (7th June 2016) - Li, M J; Xu, L P; Shi, K; Zhang, J Z; Chen, X F; Hu, Z G; Dong, X L; Chu, J H
Abstract: The thermal evolutions of optical properties and phase transitions of PbZr1− x Ti x O3 (PZT) ceramics as the functions of Ti compositions have been systemically explored by means of temperature dependent ellipsometric spectra and first-principles calculations. Two interband electronic transitions have been obtained by fitting the second derivatives of the complex dielectric functions and the physical origins can be explained with the aid of theoretical calculations. Based on the interband transitions, the phase diagram of PZT ceramics can be well-established. Importantly, dramatic Zr-rich ion clusters at 70 K and two intermediate regions are captured. The Zr-side intermediate phase is attributed to the tilting competitions of high [FER(HT) ] and low [FER(LT) ] temperature rhombohedral structures. Moreover, a wider range of the monoclinic (M) region from x = 0.28 to 0.50 has been determined than previously reported. Interestingly, one can conclude that a more superior performance of PZT may be obtained with the larger M domains relying on external strains or fields.